A comprehensive review of Rubia cordifolia L.: Traditional uses, phytochemistry, pharmacological activities, and clinical applications - Wen, Min; Chen, Qi; Chen, Wang; Yang, Jing; Zhou, Xiaogang; Zhang, Chunxiang; Wu, Anguo; Lai, Jia; Chen, Jianping; Mei, Qibing; Yang, Shuo; Lan, Cai; et al. (Frontiers in Pharmacology, 2022)
Rubia cordifolia (family: Rubiaceae) Linn. (R. cordifolia) is a perennial herb climbing vine. As the main part of the traditional Chinese medicine, the rhizome has a long history. A great number of literary studies have reported that it can be used for the improvement of blood circulation, hemostasis, activation of collaterals, etc. When it comes to the wide application of R. cordifolia in traditional medicine, we systematically review its traditional uses, phytochemistry and pharmacological effects. Literatures were systematically searched using several scientific databases, including China National Knowledge Infrastructure (CNKI), Baidu Scholar, PubMed, Web of Science, and other professional websites. Kew Botanical Garden (https://powo.science.kew.org/) and the iPlant (http://www.iplant.cn/) were used for obtaining the scientific names and plant images of R. cordifolia. In addition, other information was also gathered from books including traditional Chinese herbal medicine, the Chinese Pharmacopoeia, and Chinese Materia Medica. So far, many prescriptions containing R. cordifolia have been widely used in the clinical treatment of abnormal uterine bleeding, primary dysmenorrhea and other gynecological diseases, allergic purpura, renal hemorrhage and other diseases. The phytochemistry studies have reported that more than 100 compounds are found in R. cordifolia, such as cyclic peptides, terpenes, polysaccharides, trace elements, flavonoids, and quinones. Among them, quinones and peptides are the types of components with the highest contents in R. cordifolia. The modern pharmacological studies have revealed that R. cordifolia and its derived components have anti-tumor, anti-oxidative, anti-platelet aggregation, and anti-inflammatory effects. However, most studies are preclinical. The pharmacological mechanism of R. cordifolia has not been thoroughly studied. In addition, there are few pharmacokinetic and toxicity studies of R. cordifolia, therefore the clinical safety data for R. cordifolia is lacking. To sum up, this review for the first time summarizes a systemic and integrated traditional uses, chemical compositions, pharmacological actions and clinical applications of R. cordifolia, which provides the novel and full-scale insight for the drug development, medicinal value, and application of R. cordifolia in the future.